GAMBARAN KEJADIAN MOMNESIA PADA IBU HAMIL DI KABUPATEN INDRAMAYU - Yati Nurhayati; Purwandyarti Apriliani; Meran Dewina (JURNAL KESEHATAN INDRA HUSADA, 2022)
Background : Momnesia is memory problems in pregnant women. Incidence Momnesia during pregnancy, one of the reasons is hormonal changes. The emotional changes that occur during pregnancy, the concept of preparing for parents triggers a psychological response and introspection. Research by Debra et al shows that there are cognitive changes during preconception, as well as various cognitive disorders momnesia during pregnancy. The novelty of this study, there are not many studies regarding the incidence of momnesia in pregnant women in Indonesia. The purpose of this study was to know the number of pregnant women who experience momnesia in Indramayu.Method : This study conducted using a descriptive methods with subjects were pregnant women who live in the Margadadi Health Center and Pasekan Public Health Center who are fulfilling the inclusion and exclusion criteria, from March to September 2020 by purposive sampling. This research has received ethical approval from STIKes BTH Tasikmalaya N0.030/kepk-bth/VI/2020.Results : The results, found that 129 out of 138 pregnant women not experienced symptoms of momnesia in Indramayu. Conclusion : The conclusion of this study is 93,48% of pregnant women not have symptoms ofmomnesia in Indramayu.